Knowledge and practices of open science among scholars and researchers in Tanzania - David, Aneth, Bella; Alimohamed, Mohamed; Modern, Grantina; Buhomoli, Obadia, Shadrack; Muneja, Paul (My University, 2022)
The Open Science (OS) movement has been spreading rapidly among researchers with positive outcomes on accessibility of scientific knowledge. However, there is no clear evidence on the level of awareness and types of OS practices among scholars and researchers in Tanzania, potentially missing an opportunity to reap the rewards of the movement to scholarly pursuits. This study investigated the level of awareness of OS and practices among Tanzanian scholars and researchers. Findings of a digital survey conducted for three months and recruited 144 respondents, show a high level of awareness of the term OS for 84% of respondents, most of them having encountered it from peers or online sources including social media. About 69% of respondents were male while about 44% of respondents were early career professionals. Open access (OA) publishing was the most common OS activity practised by respondents, highlighting both the need to create awareness on other practices and an entry point for knowledge expansion. However, respondents highlighted the barriers to spreading of the OS movement in the country including lack of awareness, knowledge and skills, the lack of institutional support and concerns over data security and ownership. Findings of this study establish OA as the most common and important OS practice among Tanzanian scholars. They show the importance of online resources and peers to peer learning and in spreading OS awareness. The study also reveals several areas of advocacy and including setting supportive institutional policies and building infrastructure to support OS practices. We recommend establishment of robust guidelines, institutional support and clear opportunities to incentivize individuals to adopt OS practices so as to achieve the momentum required to scale the movement beyond OA.
Keywords: Open Access; Open Science; Open Science Tanzania; OS